Pendampingan Sertifikasi Halal melalui Skema Self-declare untuk Meningkatkan Kredibilitas dan Jangkauan Pasar UMKM - Rahmawati, Riris Trimaulida; Utami, Mega Dewi Sri; Trisetyo, Febiola Anggun; Mutmainah, Siti; Anshari, Muhammad; Setiawan, Firman (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This service explores the implementation of halal product certification through the Self-declare scheme for Micro, Small, and Medium Enterprises (MSMEs), specifically the Dodol Siwalan producers in Totosan Village, Batang-Batang District, Sumenep Regency. The halal certification program offered by the Indonesian government aims to facilitate the halal certification process for MSMEs by allowing them to obtain their halal products by meeting certain requirements. Considering Indonesia's significant Muslim population and its ambition to become a global halal hub by 2024, this dedication underscores the importance of halal certification in enhancing product credibility and market reach for SMEs. The service methods used include observation, interviews, socialization, discussion, and mentoring with local SMEs, fostering a compliant and competitive food industry in Indonesia, particularly the siwalan dodol in Totosan Village, Sumenep Regency.